Let f ( x ) = x 3 + 2 x 2 + 3 x + 2 and g ( x ) be a polynomial with integer coefficients. When f ( x ) is divided by g ( x ) , it leaves quotient q ( x ) and remainder r ( x ) , both of which have integer coefficients.
If q ( x ) = r ( x ) = 1 ,then find g ( 5 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
take g(x)=-pow(x,3)-2*pow(x,2)-3x-3, when r(x)=-1. I think you missed whole numbers in the question.
We note that:
f ( x ) = q ( x ) g ( x ) + r ( x ) = q ( x ) ( g ( x ) + q ( x ) = q ( x ) ( g ( x ) + 1 )
⇒ q ( x ) f ( x ) = g ( x ) + 1
We also note that:
f ( x ) = x 3 + 2 x 2 + 3 x + 2 = ( x + 1 ) ( x 2 + x + 2 )
Assuming that q ( x ) = x + 1 as it is lower degree than x 2 + x + 2 , then
⇒ x + 1 f ( x ) = x 2 + x + 2 = g ( x ) + 1
⇒ g ( x ) = x 2 + x + 1 ⇒ g ( 5 ) = 2 5 + 5 + 1 = 3 1
I think that first, we should check that r(x) is not a constant term. Which is quite easy but necessary to prove. First, assume that r(x) is n,n belongs to integers, then we find that 1/n is also an integer which forces n=1 that is a contradiction or n=-1.But then assuming that you meant non-negative integers, then n!=-1. The next steps are already written, therefore I am not writing them again.
We have f(x)=q(x){g(x)+1} Now, x^3+2x^2+3x+2 =(x+1)^3-(x^2-1) =(x+1){(x^2+x+1)+1} Thus, by inspection; g(x) =x^2+x+1 And g(5) =31(Answer)
x 3 + 2 x 2 + 3 x + 2 = ( x 2 + x + 2 ) ( x + 1 )
By Division Algorithm f ( x ) = q ( x ) g ( x ) + r ( x ) . Since q ( x ) = r ( x ) ,
thus f ( x ) = q ( x ) g ( x ) + q ( x ) . This gives us f ( x ) = q ( x ) ( g ( x ) + 1 ) .
By inspection, g ( x ) + 1 = x 2 + x + 2 , thus
g ( x ) = x 2 + x + 1 . Hence g ( 5 ) = 3 1
Problem Loading...
Note Loading...
Set Loading...
The division algorithm gives us that f ( x ) = g ( x ) q ( x ) + r ( x ) .
Since q ( x ) = r ( x ) , we have that f ( x ) = g ( x ) r ( x ) + r ( x ) ⟶ f ( x ) = r ( x ) ( g ( x ) + 1 ) .
The Rational Root Theorem helps us determine that − 1 is a root of f ( x ) . Thus, by the Remainder Factor Theorem , x + 1 is a factor of f ( x ) , which can thus factor into f ( x ) = ( x + 1 ) ( x 2 + x + 2 ) .
We have two representations for f ( x ) , namely f ( x ) = r ( x ) ( g ( x ) + 1 and f ( x ) = ( x + 1 ) ( x 2 + x + 2 ) . Since, deg ( g ( x ) ) ≥ deg ( r ( x ) ) , it must be that g ( x ) = x 2 + x + 1 .
Hence , g ( 5 ) = 5 2 + 5 + 1 = 2 5 + 5 + 1 = 3 1